BIOLOGY AND CPUE SPATIAL DISTRIBUTION OF ESCOLAR Lepidocybium flavobrunneum (Smith, 1843) IN EASTERN INDIAN OCEAN (EVOLVING FISHERIES: TODAY’S BY-CATCH IS TOMORROW’S TARGET CATCH) - Fathur Rochman; Irwan Jatmiko; Arief Wujdi (Indonesian Fisheries Research Journal, 2016)
Discharge of by catch is a significant problem in world fishery. Every commercial fishery such as tuna longline has a suite of bycatch species, escolar fish (LEC). LEC as by catch product has received a little attention because of its lower economic value and given its importance as a secondary market. With time, however, market can become establish for this presently undesirable species. Acknowledging that today’s by catch might become tomorrow’s target fish. The aims of this study areto provide information on biological aspect and catch per unit of effort (CPUE) spatial distribution of escolar (Lepidocybium flavobrunneum) as by catch in Indonesian longline fishery operating in the Eastern Indian Ocean. Total escolar samples of 1,815 were taken from scientific observer data from 2011-2013. The study area of escolar was between 0.897-33.175°S and 85.366– 138.733°E of Eastern Indian Ocean. Results show that the escolar length (cmFL) is distributed from 27-178 cmFL (median=83 cmFL, mode=85 cmFL, mean=83.95 cmFL and n= 1.812) and dominated by the size of 85 cmFL. The length weight relationship was determined to be W=0.0002FL2.2926(W in kg, FL in cm). In terms of CPUEs distribution, the lower CPUEs(<1.0001) generally occurred near shore between Indonesia and Australia (10-20°S and 110 125°E).The highest CPUEs of escolar (>1.0001 to 7.382) generally occurred in Western Australian, precisely on grid between 10-35°S and 85-110°E. These grids would be a potential for fishing LEC with the best time to catch in June to August.